Effect of Copper and Iron Ions on the Sulphidizing Flotation of Copper Oxide in Copper Smelting Slag - Qing-qing Pan; Hui-qing Peng (Advances in Materials Science and Engineering)
The treatment of smelting slag has attracted much attention nowadays. This study investigates the influence of Na2S, CuSO4, and FeCl3 on sulphidizing flotation of copper oxide. The results show that a proper Cu2+ concentration can increase the sulphidizing effect of copper oxide, while Fe3+ inhibits the sulphidizing effect. Further analysis shows that Cu2+ ions can reduce the surface potential, increase the S2− adsorption, then generate more polysulfide, and therefore promote the sulphidizing flotation. However, Fe3+ ions would increase the surface potential, reduce the S2− adsorption, generate more sulfur element, and therefore inhibit the sulphidizing flotation.